Makna Ungkapan “Duri Dalam Daging” Menurut Paulus Dalam Surat 2 Korintus 12:6-7 - Joseva, Joseva (Vieka Wahana Semesta, 2025)
In discussing this research, the researcher uses a qualitative method, and conducts a literature review as a source of material, namely by looking at various books related to the topic discussed, the Bible, journals and the Internet. The approach used is an exegetical study with word analysis and syntax analysis with the help of the Bibleworks 10 application. In the discussion of exegesis, it cannot be separated from the background of the letter 2 Corinthians, the interpretation and results of the exegesis. After conducting exegesis in the text contained in the letter 2 Corinthians 12: 6-7, it provides four important statements: First, If I want to boast, I will not be a fool, I will speak the truth. Second, But I will restrain myself, so that no one believes in me more than what they see and hear. Third, Therefore, an angel of Satan was given to me in my flesh to tempt me. Fourth, So that I do not exalt myself. Therefore it is true that the expression of the apostle Paul needs to be understood using common sense by today's servants of God. So that in his service every servant of God does not exalt himself and boast because of the advantages he has. But Jesus Christ is the one who is exalted. A servant of God should be obedient and submit to his Master.